Airway and Swallowing Outcomes Following Laryngotracheoplasty With Posterior Grafting in Children. (25th May 2021) - Kou, Yann‐Fuu; Redmann, Andrew; Tabangin, Meredith E.; Wilcox, Lyndy; Miller, Claire K.; Smith, Matthew; Myer, Charles; Hart, Catherine K.; Rutter, Michael J.; de Alarcon, Alessandro
Abstract : Objectives/Hypothesis: Evaluate swallowing and airway outcomes following laryngotracheoplasty with posterior grafting (LTP PCCG). Methods: Retrospective review of pediatric patients undergoing LTP PCCG from 2016 to 2019 at a tertiary care pediatric hospital. We included demographics, indications, approach, and revision status. We evaluated preoperative and postoperative instrumental and functional swallow evaluations, and we also gathered information on airway outcomes. Results: Thirty‐one patients were included in the study. Median (interquartile range [IQR]) age was 4.0 (2.0, 7.0) years old. Primary indication for surgery was bilateral vocal cord immobility (BVCI) in 11 (35.5%) and posterior glottic stenosis (PGS) in 20 (64.5%). Mean (standard deviation) length of follow‐up was 11.0 (8.3) months. Twelve patients had gastrostomy tubes (GT) before surgery, and no patients required placement of GT after surgery. Of the remaining 19 patients, 6 required nasogastric feeding for >4 weeks (average length 1.8 months, longest 3.5 months). At last follow‐up, 25 (80.6%) patients were primarily orally fed. Eighteen patients had tracheotomies prior to surgery. No patients without a tracheostomy required placement of tracheostomy before or after surgery and only 1 patient had a tracheostomy at last follow‐up. Average time to decannulation was 3.7 months, with surgery‐specific success of 87.1% and overall success of 96.8%. Four (12.9%) patients required a major intervention to achieve decannulation. Conclusion: LTP PCCG is an effective surgical technique to address PGS and BVCI with high decannulation rates. It may cause temporary swallowing dysfunction, but in this series a majority of children were orally fed at last follow‐up. Level of Evidence: 4 Laryngoscope, 131:2798–2804, 2021